KAJIAN HUKUM PERLINDUNGAN KONSUMEN TERHADAP PINDAH ALAMAT LAYANAN INDIHOME - Khairunnisah, (The Juris, 2021)
The internet has now become a basic need in the digital era, a smooth and strong internet network is considered to provide great benefits as a support in daily activities. In the process of installing the Internet, many providers can be used, one of which is the Indihome Internet service. In one case there was a problem, namely in the process of moving home addresses that participated at the same time in terms of changing the internet address of the indihome. The procedure is made before the process of changing the address, the consumer first makes a request by calling via the call center or can go directly to the Teklom plaza, then when the application has been received and the conditions have been fulfilled for the change of address, then an electronic contract for address change is issued. directly to onsumen via email. The issue of consumer protection is still an important issue until now, various cases of violation of consumer rights that have been going on for a long time, need to be examined critically, such as the example that has been explained by the author regarding the contract agreement for the indihome address change. The internet has now become a basic need in the digital era, a smooth and strong internet network is considered to provide great benefits as a support in daily activities. In the process of installing the Internet, many providers can be used, one of which is the Indihome Internet service. In one case there was a problem, namely in the process of moving home addresses that participated at the same time in terms of changing the internet address of the indihome. The procedure is made before the process of changing the address, the consumer first makes a request by calling via the call center or can go directly to the Teklom plaza, then when the application has been received and the conditions have been met for address change, then an electronic contract for address change will be issued. directly to consumer via email.